Kerosene Oil Poisoning among Children in Rural Sri Lanka - M. B. Kavinda Chandimal Dayasiri; Shaluka F. Jayamanne; Chamilka Y. Jayasinghe (Hindawi Limited, 2017)
Introduction. Kerosene oil poisoning is one of common presentations to emergency departments among children in rural territories of developing countries. This study aimed to describe clinical manifestations, reasons for delayed presentations, harmful first aid practices, complications, and risk factors related to kerosene oil poisoning among children in rural Sri Lanka. Methods. This multicenter study was conducted in North-Central province of Sri Lanka involving all in-patient children with acute kerosene oil poisoning. Data were collected over seven years from thirty-six hospitals in the province. Data collection was done by pretested, multistructured questionnaires and a qualitative study. Results. Male children accounted for 189 (60.4%) while 283 (93%) children were below five years. The majority of parents belonged to farming community. Most children ingested kerosene oil in home kitchen. Mortality rate was 0.3%. Lack of transport facilities and financial resources were common reasons for delayed management. Hospital transfer rate was 65.5%. Thirty percent of caregivers practiced harmful first aid measures. Commonest complication was chemical pneumonitis. Strongest risk factors for kerosene oil poisoning were unsafe storage, inadequate supervision, and inadequate house space. Conclusions. Effect of safe storage and community education in reducing the burden of kerosene oil poisoning should be evaluated. Since many risk factors interact to bring about the event of poisoning in a child, holistic approaches to community education in rural settings are recommended.